EFL STUDENTS' PERCEPTION ON THE TYPE OF TEACHER QUETIONS: A QUALITATIVE DESCRIPTIVE STUDY - Yahya, Roza Auliya; Kaniadewi, Nita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
This study explores high school EFL students' perceptions of teacher questioning strategies, focusing on question types, their use, and effectiveness in enhancing engagement and comprehension. Questioning techniques are vital in EFL classrooms, promoting interaction, critical thinking, and understanding. This qualitative descriptive study involved ten first-year high school students from SMAN 58 Jakarta, using observations, semi-structured interviews, and documentation of student grades. The findings reveal that teachers frequently use open-ended questions at the beginning of lessons to review previous material and stimulate critical thinking, with students preferring these types of questions for fostering broader thinking and active participation. Teachers predominantly use Lower Order Thinking Skills (LOTS) questions initially, shifting to Higher Order Thinking Skills (HOTS) questions during exams. Students perceive that teacher questioning techniques significantly enhance their understanding and engagement, aligning with previous research indicating that effective questioning leads to better outcomes in EFL classrooms. The study underscores the importance of employing diverse questioning strategies to support language development and academic achievement, providing valuable insights into effective pedagogical practices for EFL teachers. This research highlights the need for strategic questioning to enhance student learning experiences, motivation, and comprehension.